Making architecture compete: open-ended accumulation meets objectification and singularisation in the UK construction industry. Issue 5 (2nd September 2016) - Gottschling, Paul
ABSTRACT: Sociologists over the last two decades have taken inspiration from actor-network theory to suggest that competition, like 'the market', takes place through a dynamic of detaching objects from one set of relations and reattaching them within another: objectification and singularisation. Yet there has been little theorisation of how competition differs between situations. To approach this question, we can ask how competition, as a process of objectification and singularisation, interacts with other patterns of movement. Ethnographers have described one such pattern in the everyday work of architects. Here a building emerges from an ever-increasing number of 'versions', images and models, in an open-ended accumulation. This study considers the interaction between, first, the objectification and singularisation of competition and, second, the open-ended accumulation of architectural work. To do so, I examine architectural competitions in the UK. I draw from document analysis of one competition for a school in northern England, as well as interviews with architects about their work on competitions. This study concludes that architectural competitions repeat the multiplicity of architectural work but in a more delimited form. Multiplicity is not 'cut-off' so much as winnowed down through an explicit process of selecting images and blocks of text.